Densely populated tiny RuO2 crystallites supported by hierarchically porous carbon for full acidic water splitting - Yu, Bo; Jin-Hang, Liu; Guo, Shuaibiao; Huang, Guanlin; Zhang, Shengjia; Chen, Shuangqiang; Li, Xiaopeng; Wang, Yong; Li-Ping, Lv (Materials horizons, 2023)
The exploitation of highly active bifunctional electrocatalysts for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in acidic media has been a subject receiving immense interest. However, the existing catalysts usually suffer from low catalytic efficiency and poor corrosion resistance under acidic conditions. Herein, we report a facile molten salt method to fabricate ruthenium dioxide nanoparticles supported by hierarchically porous carbon (RuO2/PC) as a bifunctional electrocatalyst for full water splitting under strong acidic conditions. The formation of a densely populated nanocrystalline RuO2/carbon heterostructure helps expose catalytic sites, accelerates the mass transfer rate, and further enhances the acid resistance of RuO2 nanoparticles. The as-synthesized RuO2/PC consequently exhibits superior catalytic performance for the OER with an overpotential of 181 mV upon 10 mA cm−2 compared to that of the commercial RuO2 (343 mV) and a comparable performance to Pt/C for the HER (47.5 mV upon 10 mA cm−2) in 0.5 M H2SO4. The RuO2/PC shows promising stability with little degradation over ∼24 h. Impressively, the water electrolyzer based on RuO2/PC shows an overpotential of 326 mV at 10 mA cm−2, much lower than that of the electrolyzer based on the combination of Pt/C and RuO2 (400 mV), indicating its great potential towards practical application.